Pelestarian Kotagede Sebagai Pusat Pariwisata Heritage Kota Tua Di Yogyakarta - Fathurrahman Nurul Hakim - AKPAR BSI Yogyakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2018)
Abstract - Kotagede is a former Islamic Mataram kingdom where many historical and cultural heritage created in this area, both cultural heritage which is managed by the government or individuals, the Foundation kantil, foundations observer and preserver of cultural heritage in Kotagede, recorded prior to the May 2006 earthquake was recorded 151 residential houses shaped  joglo cultural heritage preserved, but after the earthquake only 88 house of cultural heritage restoration works in the community after an earthquake is a lot of cultural heritage. Conservationists  popping thing that makes fit with the concept of community-based conservation, where the community is expected to contribute actif in the preservation and find yourself solutions to problems that occur. The role of government is expected to facilitate the training is held by the community in particular and society in the preservation Kotagede  although this has been done by the department  BP3 (Departement ancient heritage conservation) DIY but only on technical maintenance, but preparation of  Tourism human resources in the sustained not seem real, it is still in need of a more mature preparation, especially in the regeneration of the preservation of cultural heritage and art that have  Kotagede to sustainable tourism in order to meet people prospering Kotagede.Keyword :Conservation, Community, Tourism Sustainable